Luigi Einaudi : selected economic essays, volume 2 - Faucci, Riccardo; Marchionatti, Roberto; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Luigi Einaudi (1874-1961) was a leading liberal Italian economist, economic historian and political figure: Governor of the Bank of Italy, Minister for the Budget and President of the Italian Republic. He was a prolific writer in all fields and his writings testify to his outstanding contribution to economics during his long career.
Keywords: Economic history; Economic theory; Macroeconomics; Economic policy; Regional economics; Spatial economics